Serum Uric Acid and Its Correlation with Blood Pressure in Hypertensive Patients. A Comparative Study - Zahid Habib Qureshi, Nabeela Yaseem, Bakhtawar Farooq, Abida Jaffar, Muhammad Farhan, Ejaz Hussain Sahu (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hypertension is a major global health problem and an important risk factor for cardiovascular morbidity and mortality. In recent years, serum uric acid (SUA) has emerged as a potential biomarker linked to vascular dysfunction and elevated blood pressure. However, the association between SUA and hypertension remains controversial, particularly in South Asian populations where the burden of both hypertension and metabolic disorders is rising. Objective: This study aimed to compare serum uric acid levels between hypertensive patients and normotensive controls and to evaluate the correlation of SUA with systolic and diastolic blood pressure. Methods: A comparative cross-sectional study was conducted at Multan Medical and Dental College (MMDC), Multan, in collaboration with Nishtar Medical University, Multan, from January 2022 to January 2023. A total of 100 participants were included, consisting of 50 hypertensive patients and 50 normotensive age- and sex-matched controls. Blood pressure was recorded according to WHO guidelines, and fasting blood samples were collected to measure serum uric acid using the Uricase-Peroxidase enzymatic colorimetric method. Data were analyzed using SPSS version 26, with t-tests for group comparisons and Pearson’s correlation for association analysis. Results: Mean SUA levels were significantly higher in hypertensive patients (6.8 ± 1.3 mg/dL) compared to controls (5.1 ± 1.1 mg/dL, p < 0.001). A significant positive correlation was observed between SUA and systolic blood pressure (r = 0.42, p = 0.002) and diastolic blood pressure (r = 0.36, p = 0.009) in hypertensive patients, whereas no significant correlation was noted in controls. Conclusion: Serum uric acid is elevated in hypertensive patients and shows a positive correlation with both systolic and diastolic blood pressure. Monitoring SUA may provide an additional tool for risk assessment and management in hypertensive individuals. Keywords: Hypertension, Serum uric acid, Blood pressure, Cardiovascular risk, Comparative study